The design of business : why design thinking is the next competitive advantage - Martin, Roger L. (Harvard Business Press, 2009)
Most companies today have innovation envy. Many make genuine efforts to be innovative: they spend on R & D, bring in creative designers, hire innovation consultants; but they still get disappointing results. Roger Martin argues that to innovate and win, companies need 'design thinking'.